José Saramago's relationship with dictionaries - José Barbosa Machado (Études romanes de Brno)
José Saramago includes in his works a series of comments about the dictionaries that he consulted in his writing work whenever he had a doubt about a word or expression that he intended to use. Dictionaries function as lexicographic and semantic authorities. Expressions such as "the dictionaries affirm" (Ensaio sobre a Lucidez), "the dictionary says" (O Ano da Morte de Ricardo Reis; Manual de Pintura e Caligrafia), "the dictionary tells me" (Deste Mundo e do Outro), "it is in the dictionary" (Deste Mundo e do Outro), "they are found in dictionaries" (O Homem Duplicado), "According to the dictionaries" (A Bagagem do Viajante), "one day he went to see in the dictionary if the word existed" (A Jangada de Pedra), etc. prove this. In the children's story A Maior Flor do Mundo (2001), Saramago even recommends that children go to the dictionary: "Now some difficult words will start to appear, but anyone who doesn't know should go look in the dictionary or ask the teacher". The great news about dictionaries is that, unlike other writers, who use them without making it known in the text they write, Saramago openly says that he uses them and even discusses and comments on what he finds in them. The objective of this study will be to identify passages in Saramago's works with direct reference to dictionaries and to prove the author's interest in issues of lexicography and semantics of the Portuguese language.